First record of helminth parasites in Fulica ardesiaca (Aves: Rallidae) from Peru: Pantanos de Villa – Lima - Guillén, Gisella (2003)
Two trematodes and one cestode of Fulica ardesiaca from Pantanos de Villa, Lima, Peru are registered at first time. Total of 698 parasites were counted, 529 individuals of Notocotylus pacifera, 149 individuals of Psilostomum sp. and 20 individuals of Diorchis Americana. This work is the first report in F. ardesiaca from Peru; while Psilostomum sp. and D. americana are first registrations for the Peruvian’s helminthes.